Value Related Practices Used by Teacher Educators at a Public University, Islamabad - Munazza Mahmood (Journal of Education and Educational Development, 2020)
Values play a vital role in any teacher-training program. The value practices, used by teacher educators affect students’ understanding and practicing of values. This study aimed to explore the value related practices of teacher educators and to rank the value practices of education programs at a public sector university. Survey method was used for the study and the population comprised prospective teachers of education program at the university.100 prospective teachers were selected through simple random sampling technique. Data were collected through questionnaire and analyzed by using mean. It was found that there were several value related practices used by teacher educators such as realness, prizing, empathic understanding, fully functioning person, humility, lovingness, courage – overcoming one’s own fears, tolerance, decisiveness, living the tension between patience and impatience and the joy of living. With reference to ranking, realness stood above all other values. It is recommended that there may be more focus on different value related practices and that these are introduced in contents of teacher education program.
Keywords: practices; prospective teachers; teacher educators; values